REVOLUSI PENDIDIKAN: MENAVIGASI ERA BARU DENGAN KURIKULUM MERDEKA DI SEKOLAH DASAR - Salim, Nur Agus (Fakultas Keguruan dan Ilmu Pendidikan, 2023)
The Merdeka Curriculum is designed to promote 21st century skills such as critical thinking, creativity, and collaboration, as well as offering an approach that is more adaptive and relevant to the needs of today's students. Through literature analysis and case studies, this research identifies the main challenges in implementing the Merdeka Curriculum, including the need for comprehensive teacher training, infrastructure adaptation, and alignment with national education standards. The research results show that the Merdeka Curriculum has significant potential to improve the learning experience in elementary schools, but its success is highly dependent on effective implementation strategies and broad support from all parties involved. This research emphasizes the importance of collaborative approaches in education, recognizing that educational transformation requires active participation from policymakers, educators, students, and parents.